An Exploratory Taxonomy of Business Games. (October 2013) - Greco, Marco; Baldissin, Nicola; Nonino, Fabio
This article proposes a business game taxonomy. The taxonomy creates a comprehensive definition of business games in general and identifies their parameter-defining characteristics. A successful taxonomy can facilitate the comparison of different game-based educational tools and can direct application-based research to a game's most learning-associated components. The field's existing taxonomies within the literature are inadequate for both purposes. The genesis of our five-part taxonomy of business games was both literature-based and intuitive. It is hoped that this taxonomy will serve to develop a global database to be built collaboratively by the community of business game users and developers.